2019
DOI: 10.1002/jhbp.652
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of pancreaticoduodenectomy following preoperative biliary drainage considering major morbidity and postoperative survival

Abstract: BackgroundThe present study aimed to determine the optimal timing of pancreaticoduodenectomy (PD) following preoperative biliary drainage (PBD) with consideration of postoperative morbidity and survival.MethodsBetween January 2007 and December 2015, consecutive 1,568 patients underwent PD at a single institution. Their data were reviewed retrospectively.ResultsOf all, 831 patients underwent PBD. The mean duration between drainage and surgery was 16.9 days. Regarding postoperative outcomes, length of hospital s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
2
10
1
Order By: Relevance
“… 26 However, most patients did not reach this rate in real clinical practice. 9 , 13 , 24 Thus, a cutoff point of more than 20% bilirubin decrease within 7 days suggested by the European Society of Gastrointestinal Endoscopy (ESGE) guideline was adopted in this study as an adequate bilirubin drainage. 20 The current study’s result showed that patients who had major morbidity were less likely to have come from the adequate biliary drainage rate group than the inadequate group.…”
Section: Discussionmentioning
confidence: 99%
“… 26 However, most patients did not reach this rate in real clinical practice. 9 , 13 , 24 Thus, a cutoff point of more than 20% bilirubin decrease within 7 days suggested by the European Society of Gastrointestinal Endoscopy (ESGE) guideline was adopted in this study as an adequate bilirubin drainage. 20 The current study’s result showed that patients who had major morbidity were less likely to have come from the adequate biliary drainage rate group than the inadequate group.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, previous studies of the impact of PBD on long-term survival in all patients have suffered from shortcomings in the methods used to select cases. Furthermore, the duration of PBD, which was rarely included in the previous research, may also influence the long-term outcome in patients with obstructive jaundice based on the recent studies ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, in recent years, several PBD methods were simultaneously employed, and new drainage brackets are coming onto the scene [17,18]. The management of obstructive jaundice is complicated and involves not only surgeons and medical centers but also the entire healthcare system [19]. Hegel's principle "what exists is reasonable" is thought to be applicable worldwide, but we found a more accurate observation by examining the current methods in some clinical settings.…”
Section: Discussionmentioning
confidence: 88%